Simulation comparison of InGaP/GaAs HBT thermal performance in wire-bonding and flip-chip technologies. (November 2017) - d'Alessandro, Vincenzo; Catalano, Antonio Pio; Magnani, Alessandro; Codecasa, Lorenzo; Rinaldi, Niccolò; Moser, Brian; Zampardi, Peter J.
Abstract: This paper presents an extensive numerical analysis of the thermal behavior of InGaP/GaAs HBTs for handset applications in a laminate (package) environment. Both wire-bonding and flip-chip technologies are examined. The combination between an accurate, yet fast, simulation capability and the Design of Experiments technique is employed to quantify the impact of all the key technology parameters and explore a wide range of operating conditions. Highlights: An accurate analysis of the thermal behavior of packaged InGaP/GaAs HBTs is performed. The analysis is conducted by combining an advanced simulation capability and the DOE. The impact of all the key technological parameters of die and laminate is examined. The wire-bonding and flip-chip packaging solutions are thermally compared. DOE-based expansions are derived for a fast assessment of thermal resistances.